2019
DOI: 10.1103/physrevb.100.035406
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic nodal-line metal in monolayer h -InC

Abstract: Based on first-principles calculations, we predict a new two-dimensional ferromagnetic material that exhibits exotic Fermi surface topology. We show that monolayer hexagonal indium carbide (h-InC) is thermodynamically and dynamically stable, and it energetically favors the ferromagnetic ordering of spins. The perfectly planar geometry in two dimensions, together with ferromagnetism, gives rise to a unique opportunity to encounter intriguing electronic properties, captured in the Fermi surface and band topology… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 121 publications
0
8
0
Order By: Relevance
“…This invariance of MAE in the x-y plane is likely to be due to the fact that the FM instability is induced by the highly localized Fe d z 2 and d yz orbitals near E F [see Figs. , as well as ∼400 µeV of the previously predicted 2D nodal-line materials InC [27] and MnN [52]. Therefore, Fe 2 Ge and Fe 2 Sn monolayers can be classified as hard magnetic 2D materials, which barely change the spin orientations via externally applied magnetic field.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…This invariance of MAE in the x-y plane is likely to be due to the fact that the FM instability is induced by the highly localized Fe d z 2 and d yz orbitals near E F [see Figs. , as well as ∼400 µeV of the previously predicted 2D nodal-line materials InC [27] and MnN [52]. Therefore, Fe 2 Ge and Fe 2 Sn monolayers can be classified as hard magnetic 2D materials, which barely change the spin orientations via externally applied magnetic field.…”
Section: Resultsmentioning
confidence: 84%
“…Most of the NLS states have so far been experimentally observed in three-dimensional (3D) materials such as PtSn 4 [21], ZrSiS [22], and PbTaSe 2 [23]. However, recent theoretical and experimental studies of such NLS states have been extended to 2D monolayers [24][25][26][27] whose electronic properties can be easily tuned by mechanical strains [28,29]. Based on the combined angle-resolved photoemission spectroscopy measurements and density-functional theory (DFT) calculations, Feng et al [24] reported the presence of Dirac nodal lines (DNLs) in Cu 2 Si monolayer which is composed of a honeycomb Cu lattice and a triangular Si lattice.…”
Section: Introductionmentioning
confidence: 99%
“…The second type with T S x symmetry (and with broken P T ) also works, since T S x itself is a kind of magnetic symmetry and is compatible with certain antiferromagnetic configuration. So far, magnetic Weyl-line material candidates have been proposed for the first type, e.g., in monolayer MnN [87], CrN [88], AgN [89], CsS [90], CoSe [91], InC [92], and K 2 N [93]. Fig.…”
Section: E-ementioning
confidence: 99%
“…The glass transition temperature (T g ) of OPTT film could not be found during the first heating, which is a typical characteristic of an OPTT film with a draw ratio of at least three times. [20][21][22][23] Crystallinity was calculated based on 145.63 J/g for the 100% crystalline PTT. 24 The calculated percent crystallinity of OPTT using DSC was 36.5%.…”
Section: General Properties Of Optt Filmmentioning
confidence: 99%